Andragogy and Financial Literacy in Indonesia: An Integrative Review of Adult Education Practices - Illa Susanti; Kamil, Mustofa; Wahyudin, Uyu; Saripah, Iip; Gupta, Sachin (Journal of Nonformal Education, 2026)
Background – Financial literacy is an increasingly important adult capability because household decisions now combine budgeting, saving, borrowing, investment, and digitally mediated financial services. In Indonesia, these decisions are shaped by uneven access to financial services, differences in digital competence, and the financial management needs of households and micro, small, and medium enterprises. Research Urgency – Recent Indonesian studies are distributed across financial inclusion, fintech adoption, MSME finance, digital literacy, and community education. The evidence is less often synthesized from an adult-learning perspective that asks how relevance, experience, participation, cultural context, mentoring, and evaluation shape financial learning. Research Objectives – This review synthesizes recent evidence on adult financial literacy in Indonesia, identifies andragogical principles that are visible in effective educational practice, examines digital and cultural conditions that affect participation, and proposes implications for nonformal and community-based financial education. Research Method – An integrative review was conducted using 54 peer-reviewed and DOI-traceable publications from 2022–2026. Indonesian studies were prioritized for contextual evidence, while recent international studies were used to interpret financial literacy, digital financial capability, and adult-learning design. Findings were organized through thematic comparison rather than meta-analysis. Research Findings – Five recurring design requirements were identified: problem-centered learning tied to immediate financial decisions; use of learners’ prior experience; guided practice and reflection; support for digital financial capability and risk awareness; and contextualization through community, livelihood, and, where appropriate, Islamic financial values. Evidence also indicates that one-off knowledge transfer is insufficient when programs lack mentoring, accessibility, and follow-up evaluation. Research Conclusion – Andragogy is most useful as a design framework for financial education rather than as a stand-alone explanation of financial behavior. Adult financial literacy programs are more defensible when practical learning, digital inclusion, culturally responsive facilitation, and sustained support are connected to observable financial practices. Research Novelty/Contribution – This review develops a community-based andragogical framework for adult financial literacy education in Indonesia. The framework integrates problem-centered learning, prior experience, guided practice, digital financial capability, culturally responsive facilitation, mentoring, and outcome-based evaluation. It extends existing financial-literacy research by positioning community learning infrastructure as a mechanism that connects financial knowledge with observable financial practices.